The Use of Digital Inhalers (Smart Inhalers) in the Management of the Chronic Obstructive Pulmonary Disease Patient: A literature review - Dewa Ayu Ari Rama Dewi; Tuti Herawati (Journal of Nursing Care, 2023)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic non-communicable lung disease, where airflow obstruction occurs in the respiratory tract, is non-reversible or partially reversible, which is an inflammatory response. Morbidity, mortality and disease progression can be rapid in the event of an acute exacerbation, but can be prevented with appropriate management. Purpose: to identifyi the use of digital inhalers in the management of COPD patients The study used a non-systematic literature review method conducted online in the 2018-2022 database..Results: Many tools and technologies have been developed for COPD management. The digital inhaler app improves COPD monitoring by supporting proper use of inhalers, monitoring medication adherence with remote monitoring. Then the data is sent to the server which automatically updates the patient's medical records. The data can be analyzed by health workers to then provide feedback to users. Literature study shows that the use of digital inhalers improves dosing accuracy, therapy adherence and early detection of disease worsening